Complex mixtures : methods for in vivo toxicity testing - National Research Council (U.S.). Committee on Methods for the In Vivo Toxicity Testing of Complex Mixtures (Washington, D.C. : National Academy Press, 1988)
Addresses the problem of identifying and classifying complex mixtures, investigating the effect of exposure, and the research problems inherent in testing their toxicity to human beings. A series of case studies is presented, including one that examines the cofactors of alcohol consumption and cigarette smoke.
1 Front Matter; 2 Executive Summary; 3 1. Introduction; 4 2. Concepts for Analyzing Human Exposure to Complex Chemical Mixtures; 5 3. Testing Strategies and Methods; 6 4. Sampling and Chemical Characterization; 7 5. Interpretation and Modeling of Toxicity-Test Results; 8 Appendix A: Origins of Complex Mixtures; 9 Appendix B: Case Studies Establishing Active Agents and/or Interactions in Complex Mixtures; 10 Appendix C: Case Studies on Strategies for Testing the Toxicity of Complex Mixtures; 11 Appendix D: Predicting the Joint Risk of a Misture in Terms of the Component Risks; 12 Appendix E: Cancer Models; 13 Appendix F: Developmental Toxicology; 14 Appendix G: Empirical Modeling of the Toxicity of Mixtures; 15 Index
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: Toxicity testing -- In vivo -- Evaluation; Environmental Pollutants -- analysis; Environmental Pollutants -- toxicity; Toxicology -- methods; Toxicology -- standards; Toxicité in vivo -- Évaluation.; MEDICAL -- Toxicology; Toxicologie; Pollution; Evaluation; Toxicity testing -- In vivo -- Evaluation; Toxicity testing -- Evaluation; Electronic book